The Multifaceted Role of IT in Crisis Management: Lessons from the Asian Tsunami Disaster - PAN, Gary (Institutional Knowledge at Singapore Management University, 2011)
The occurrence of many large-scale crises in recent years has ignited significant public concerns.1 While crisis prevention is traditionally viewed as important, appropriate crisis response is regarded as even more critical, since most people recognize that the majority of disasters are both unpredictable and unpreventable. In any crisis response, information management is critical, as decision making is constrained by time urgency. The article is focused less on crisis preparedness and more on ingenuity during a crisis. The nature of crises and the resultant information needs and stakeholders cannot be predicted in advance, but capable and agile IT departments and personnel can improvise to provide quick crisis management support. To illustrate, the case study of Singapore's role in the response to the Asian tsunami disaster of 2004-2005is used. In particular, Singapore's Defence Science & Technology Agency (DSTA) and how it was able to quickly develop and deploy a crisis case management system that formed the foundation of the UN's crisis response center operations.